Use of coagulant and zeolite to enhance the biological treatment efficiency of high ammonia leachate - Ahn, DH; Chung, YC; Chang, WS (MARCEL DEKKER INC, 2002)
Most landfill leachates in Korea, herein defined as the contaminated liquid resulting from the percolation of water through a landfill, are high in ammonium nitrogen, which inhibits biological treatment processes and deteriorates rivers. A laboratory experiment investigated the effect of pre-removal of ammonium nitrogen using zeolite on the efficiency of organic treatment of the following activated- sludge process. Ferric chloride was initially used as a coagulant for solids removal. A clinoptilolite and mordenite rich rock from the Guryongpo area, the Yeongil Basalt, in Korea, reduced the ammonia nitrogen concentrations of leachate from 1300-1500 to 110-130mg/l in a 24h batch operation. Three activated sludge reactors were operated to compare treatment efficiency under different influent conditions. In reactor 1, leachate having high concentration of chemical oxygen demands (COD) and suspended solids (SS) was directly fed to the reactor without pretreatment. The supernatant, after the coagulation process that remove some suspended solids and COD, was fed to reactor 2. As the use of coagulation process alone is not effective to remove ammonium nitrogen, supernatant treated by both coagulation focusing on the removal of COD and the zeolite concentrating on the removal of ammonium nitrogen was fed to reactor 3. As the result of experiment, greater efficiency in lowering the chemical oxygen demand (83%, influent COD; 1800-3000mg/l, effluent COD; 300-500mg/l) was achieved in reactor 3. Meanwhile, 63% (influent COD; 4000-5000 mg/l, effluent COD; 1470-1840 mg/l) and 66% (influent COD; 2400-3300 mg/l, effluent COD; 820-1100 mg/l) removal efficiency of COD were achieved in reactors 1 and 2, respectively. Thus, ammonia pre-removal by zeolite remarkably improved the lowering of chemical oxygen demand and the solids separation in the activated sludge process.
Keywords: NITROGEN REMOVAL